Sound Behaviour of Concrete Churches. The Church of Santa Cruz de Oleiros - BUENO, Ana María; GALINDO, Miguel; LEÓN, Ángel Luis (Archives of Acoustics, 2018)
The church of Santa Cruz de Oleiros, Spain (1967) shows architect Miguel Fisac’s perception of sacred space after the Second Vatican Council. In this place of worship, the architect responded to the new liturgical guidelines combining geometry and architectural forms with the material of the moment, concrete. However, ordinary religious celebrations reveal acoustic deficiencies for the main use of the building. This fact is corroborated by acoustic measurements in situ. With a methodology that uses simulation techniques for the sound field, the analysis of the current acoustic behaviour of the room will serve as the basis for an acoustic rehabilitation proposal aimed at improving the acoustic conditions and so, the functionality of the church.